Enhanced electrical and mechanical properties of graphene/copper composite through reduced graphene oxide-assisted coating - Yuzhe Wang; Haoyan Cheng; Bo Sun; Shuaiyu Ma; Jiangyi Guan; Zhonghan Jiang; Kexing Song; Hao Hu (Journal of Materials Research and Technology, 2024)
Modifying the surface of metallic materials with graphene (Gr) holds significant potential for achieving high electrical conductivity in metal-based composites, leveraging the synergistic effect of the high carrier concentration in metals and the high carrier mobility of Gr. However, the strong van der Waals forces and large specific surface area of Gr sheets often lead to agglomeration in slurrys, adversely affecting the arrangement of Gr layers within the coating structure. In this study, we introduce reduced Gr oxide (rGO) into the Gr slurry to enhance the electrostatic stability and dispersion of Gr sheets through π-π interactions. By precisely controlling the composition of the coating, a compact, low-roughness coating was prepared on the surface of the copper (Cu) wire. The fabricated Gr/rGO/Cu composite wire exhibited a high conductivity of 104.2% IACS, with a tensile strength of 266.1 MPa and the elongation of 36.3%, respectively. This study demonstrates that the addition of rGO improves the dispersibility of Gr in the slurry, leading to a more compact and effective composite structure. The Gr/rGO/Cu composite wires exhibit superior electrical and mechanical properties, making them promising candidates for high-performance applications in electrical and electronic industries.